2009
DOI: 10.1007/s00421-009-1087-5
|View full text |Cite
|
Sign up to set email alerts
|

Freely chosen pedal rate during free cycling on a roller and ergometer cycling

Abstract: The purpose of this study was to examine the effect of regulation of work rate, computer controlled versus controlled by the subject, on the relationship between work rate, freely chosen pedal rate (FCC) and gross efficiency. Eighteen male cyclists participated in the study. One group, freely cycling (FC) on a competition bike mounted on an electromagnetic roller, could use gearing and cadence to achieve each work rate. The other group (EC) was cycling on an ergometer which enables a constant work rate, indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…This experimental result is in agreement with the result of our simplified cycling model and with the results of other theoretical studies based on muscle force-velocity properties (Kohler and Boutellier 2005;MacIntosh et al 2000;Sargeant 1994). This increasing C opt can be compared with the increasing FCC found in other experimental studies, where increasing power outputs were achieved at least in part by increasing the gear ratio of the bicycle (Harnish et al 2007;Leirdal and Ettema 2009). These studies found an increase of FCC with increasing power output of 8-13 rpm per 100 W. Our results showed a linear increase of C opt of about 11 rpm per 100 W with increasing performance level by means of increasing bLa at LT fix .…”
Section: Methodssupporting
confidence: 48%
See 2 more Smart Citations
“…This experimental result is in agreement with the result of our simplified cycling model and with the results of other theoretical studies based on muscle force-velocity properties (Kohler and Boutellier 2005;MacIntosh et al 2000;Sargeant 1994). This increasing C opt can be compared with the increasing FCC found in other experimental studies, where increasing power outputs were achieved at least in part by increasing the gear ratio of the bicycle (Harnish et al 2007;Leirdal and Ettema 2009). These studies found an increase of FCC with increasing power output of 8-13 rpm per 100 W. Our results showed a linear increase of C opt of about 11 rpm per 100 W with increasing performance level by means of increasing bLa at LT fix .…”
Section: Methodssupporting
confidence: 48%
“…To assess P max and C opt in an experimental approach, the P ext -cadence relationship must be fitted to a restricted number of measured power outputs at different cadences. Looking only at the range of cadences normally used by cyclists during cycling on level ground (70-110 rpm; (Leirdal and Ettema 2009;Lucia et al 2001;Sassi et al 2009), the simulated P ext -cadence relationship is very well fitted by a quadratic regression constrained to pass through the origin (maximal difference of 2.1 W; Fig. 3b).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that muscular strength and endurance (Ettema and Loras, 2009; Leirdal and Ettema, 2009) as well as pedaling technique (Zameziati et al, 2006; Korff et al, 2007; Leirdal and Ettema, 2011) are related to gross efficiency, and that strength training improves cycling performance (Sunde et al, 2010; Ronnestad et al, 2011). Moreover, strength training is shown to increase efficiency in the working muscle (Barrett-O'Keefe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sassi et al (2009) and Leirdal and Ettema (2009) showed that cycling speed significantly affected FCC. In both studies it was surmised that CIL played a key role in modulating FCC.…”
Section: Influence Of Road Inclinementioning
confidence: 98%